Implementation of HPV-testing for cervical cancer screening in programmatic contexts: The Jujuy demonstration project in Argentina - Arrossi, Silvina (2015)
The aim of this article is to present results of programmatic introduction of HPV testing with cytologic triage among women 30 years and older in the province of Jujuy, Argentina, including description of the planning phase and results of program performance during the first year. We describe the project implementation process, and calculate key performance indicators using SITAM, the national screening information system. We also compare disease detection rates of HPV testing in 2012 with cytology as performed during the previous year. HPV testing with cytology triage was introduced through a consensus-building process. Key activities included establishment of algorithms and guidelines, creating the HPV laboratory, training of health professionals, information campaigns for women and designing the referral network. By the end of 2012, 100% (n = 270) of public health care centers were offering HPV testing and 22,834 women had been HPV tested, 98.5% (n = 22,515) were 30+. HPV positivity among women over 30 was 12.7%, 807 women were HPV+ and had abnormal cytology, and 281 CIN2+ were identified. CIN2+ detection rates was 1.25 in 2012 and 0.62 in 2011 when the program was cytology based (p = 0.0002). This project showed that effective introduction of HPV testing in programmatic contexts of low-middle income settings is feasible and detects more disease than cytology.